Tiempo y temperatura del tostado de la almendra de melón en la reducción de toxicidad alergénica previo al cubrimiento con chocolate - Calderón Marcillo, Carmen María (2022)
The objective of this work was to determine the time and temperature of the roasting of the melon almond in the reduction of allergenic toxicity by biological reaction prior to covering with chocolate, the allergenic hemoagglutination test was carried out, by the method of Dr. Daniel Sautchuk, adapted by the company Castor Ecuatoriana S.A. and Oleaginosas del Pacífico Oleapacific S.A. in which, a bifactorial A*B arrangement was applied in a Randomized Complete Design (DCA) with three replicas and six treatments. The roasting temperature was studied at 60, 80 and 100 °C, with times of 10 and 30 minutes, for each experimental unit 25 g of almonds was used. The results of the allergenic toxicity variable were quantified in percentages. In the non-parametric kruskall Wallis test for roasting time, it showed a significant difference (p_<0.05), indicating that 30 minutes of roasting reduces allergenic toxicity; likewise, in the roasting temperature it was found that there was a significant difference in at least one of the levels, indicating that at a temperature of 80-100 °C the toxicity decreases, in the test homogeneous subassemblies the treatments that presented the lowest degree of toxicity (partial 50%) were T2 (10 min*80 °C), T3 (10 min*100 °C), T4 (30 min*60 °C), T5 (30 min*80 °C), T6 (30 min*100 °C) leaving T1 (10 min*60 °C) with a higher degree of allergenic (toxic) toxicity; because none of the treatments presented absence of toxicity, organoleptic acceptability was not performed to avoid complications in people's health.